The Applications of AI Tools in the Fields of Weather and Climate—Selected Examples - Agnieszka Krzyżewska (Atmosphere)
Large language models (LLMs) based on artificial intelligence have found applications across various sectors—including medicine, education, science, literature, and marketing. Although they offer considerable opportunities, their limitations also raise important concerns. This study evaluates several AI tools in the context of meteorology and climatology. The tools examined include ChatGPT o3-mini, o1, 4.o, 4.0; Gemini Advanced 1.5 and 2.0; Copilot; Perplexity; DataAnalyst; Consensus; ScholarGPT; SciSpace; Claude; and DeepSeek. The evaluation tasks comprised cloud recognition and classification from photographs, gap-filling in literature reviews, map creation based on provided datasets, comparative interpretation of maps, and archival data retrieval from line graphs converted to numerical data. Each task was rated on a 0–5 scale. Conducted between February 2024 and February 2025, the study found that ChatGPT o3-mini excelled in cloud classification; ChatGPT4.o and ScholarGPT produced high-quality maps; Claude 3.5 Sonnet and SciSpace provided the most detailed map descriptions; and Consensus and ChatGPT o1 were the most effective for literature review support. However, all tools performed poorly in regards to archival data retrieval, with Claude 3.5 Sonnet yielding the smallest errors. Overall, substantial progress was observed over the study period.